Enhancing Quality Education in Nigerian Unity Schools Through Effective Supervision in a Changing Environment - Briggs, Francis (Mediterranean Journal of Social Sciences, 2012)
It is the desire for the Federal Ministry of Education to improve the quality of teaching and learning in theUnity Schools. Supervision (internal and external) is an important component for quality education. Thispaper discussed the strategies for enhancing effective supervision, such as good leaders occupying principalposition, effective communication and improved curriculum. It also stated the problem associated witheffective supervision in achieving quality, which includes inadequate provision of infrastructure (buildings,learning and teaching materials), irregular training and re-training for staff and students, supervisorsfinding fault in the supervisee, partial or non implementation of proffered solutions by the government.The paper equally highlighted the usefulness of supervision and also made suggestions on how supervisioncould be improved to enhance quality education in a changing environment.